2008
DOI: 10.1097/nmd.0b013e318165c7c1
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Self-Focused Attention and Dissociation in Patients With and Without Auditory Hallucinations

Abstract: The purpose of this work was to study the relationship between self-focused attention and dissociative experiences in 4 groups of subjects: patients with a psychotic disorder who suffer from auditory hallucinations, patients with psychoses who have recovered from their hallucinations, patients with psychoses who have never had them, and a fourth nonclinical group. The private self-consciousness scale, revised version by Scheier and Carver, J Appl Soc Psychol. 1985;15:687-699, was used to measure self-focused a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
50
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(64 citation statements)
references
References 20 publications
11
50
0
3
Order By: Relevance
“…Estos resultados son coherentes con los obtenidos en otros estudios en los que encontraron, por un lado, una correlación positiva entre alucinaciones y delirios con disociación (PeronaGarcelán et al, 2010), y por otro, entre alucinaciones con absorción y despersonalización (Perona-Garcelán et al 2008. Estos resultados apoyan por un lado la hipótesis de que las alucinaciones auditivas pueden tener una base disociativa (Moskowitz y Corsten, 2007; Perona-Garcelán, Pérez-Álvarez, García-Montes y Cangas, 2015) y por otro, el papel que pueden tener la disociación como fuente de experiencias anómalas que favorece que la persona con psicosis las interprete de forma delirante (Garety et al, 2001).…”
Section: Tabla 5 Puntuaciones Medias (Dt) En La Escala De Experienciaunclassified
See 1 more Smart Citation
“…Estos resultados son coherentes con los obtenidos en otros estudios en los que encontraron, por un lado, una correlación positiva entre alucinaciones y delirios con disociación (PeronaGarcelán et al, 2010), y por otro, entre alucinaciones con absorción y despersonalización (Perona-Garcelán et al 2008. Estos resultados apoyan por un lado la hipótesis de que las alucinaciones auditivas pueden tener una base disociativa (Moskowitz y Corsten, 2007; Perona-Garcelán, Pérez-Álvarez, García-Montes y Cangas, 2015) y por otro, el papel que pueden tener la disociación como fuente de experiencias anómalas que favorece que la persona con psicosis las interprete de forma delirante (Garety et al, 2001).…”
Section: Tabla 5 Puntuaciones Medias (Dt) En La Escala De Experienciaunclassified
“…Estos resultados son coincidentes con los de Kilcommons y Morrison (2005), y Perona-Garcelán y colaboradores (Perona-Garcelán et al, 2008;Perona-Garcelán, García-Montes, et al, 2012) en sujetos con psicosis y en Perona-Garcelán et al (2013) en sujetos sanos con propensión a las alucinaciones (junto con la absorción), lo cual viene a confirmar la importancia de las experiencias disociativas para la comprensión de las alucinaciones auditivas.…”
Section: Tabla 5 Puntuaciones Medias (Dt) En La Escala De Experienciaunclassified
“…These patients also had more difficult course of the disease. Child abuse was specifically associated with positive symptoms and namely hallucinations (Perona-Garcelan et al, 2008;Read et al, 2005;Ross et al, 1994), higher levels of anxiety (Lysaker  Salyers, 2007), suicidal behavior (Roy, 2005), poorer psychosocial functioning and work performance (Lysaker et al, 2001, Lysaker et al, 2004. Janssen et al (2004) showed in a prospective study that childhood abuse is a risk factor for becoming psychotic in a later time and this relationship is dose-dependent.…”
Section: Trauma and Dissociationmentioning
confidence: 99%
“…Kilcommons & Morrison, 2005;Ross & Keyes, 2004;Moskowitz, Schafer, & Dorahy, 2008;Dorahy et al, 2009). For example, there is evidence that individuals with hallucinations have more dissociative experiences than those with a diagnosis of psychosis without hallucinations (Perona-Garcelán et al, 2008;Varese, Udachina, Myin-Germeys, Oorschot, & Bentall, 2011). There is also evidence that depersonalisation and absorption are more prevalent in individuals with hallucinations and hallucination proneness (Altman, Collins, & Mundy, 1997;Morrison & Petersen, 2003).…”
Section: Does Dissociation Mediate Voice Hearing?mentioning
confidence: 99%